Experimental Analysis of Voltage and Multi-Point Temperature Distribution in a 6S Lithium-Ion Battery Pack Under Constant Current Loading - Wildan Louise Fernando; Venugopal Thangavel; Hisyam Ma’mun (Advance Sustainable Science Engineering and Technology, 2026)
Lithium-ion batteries are widely utilized in energy storage applications; however, temperature non-uniformity remains a critical issue affecting performance, safety, and lifespan. This study presents an experimental investigation of the correlation between voltage and multi-point temperature distribution in a 6S lithium-ion battery pack under a constant ±5 A charge–discharge current. Temperature measurements were obtained from three sensor locations to capture spatial thermal variations during operation. The results reveal that the central cell consistently exhibited the highest temperature, reaching approximately 40 °C, while a maximum thermal gradient of 5.7 °C was observed across the pack. Furthermore, a positive correlation between current and temperature indicates uneven heat generation among cells. These findings provide direct experimental evidence of thermal asymmetry in multi-cell configurations and emphasize the importance of optimized sensor placement and enhanced thermal management strategies in Battery Management Systems (BMS).